مساهمةلبنان في الأنتروبولوجيا العربية - بزي, علي (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
تعتبر الجامعة اللبنانية التي تأسست منذ العام 1951، المؤسسة الأساسية التي تقوم باعداد الكادرات العلمية ذات المستوى العالي، والتي تعنى بتنظيم وادارة المعلومات والمساهمة في الاكتشاف المعرفي ونقله والمحافظة عليه. ويعتبر معهد العلوم الاجتماعية الذي انشأ في العام 1961 هو الصرح الذي تولى التعليم والبحث في ميادين العلوم الإجتماعية بشكل عام، وإعداد الدراسات الأنتروبولوجية بشكل خاص. كما لباقي الجامعات الخاصة على الأراضي اللبنانية إنتاجها الأنتروبولوجي، ولكن بقي في الإطار المحدود بالمقارنة مع الجامعة اللبنانية. للجامعة الدور في نقل المعرفة الى الطلاب، ومساعدتهم للقيام بالابحاث التي تحدد وتجيب عن المشكلات، وهي التي تنظم المعلومات وتديرها. للباحثين دور اساسي في تقديم الإجابات والحلول العملية لمساعدة صانعي القرار على إنجاز الأهداف الاقتصادية والتربوية والثقافية والاجتماعية.... The LebaneseUniversity, foundedsince 1951, is the primary institution thatprepares the LebaneseUniversity High-levelscientific cadres, which are concernedwithorganizing and managing information and contributing to knowledgediscoveryKeepit. The Institute of Social Sciences, foundedin 1961, is the edifice of educationResearch in the fields of social sciences in general, and the preparation of anthropologicalstudies in particular. How the rest The privateuniversities on the Lebaneseterritory have theirownanthropological production but remain in the framework ofLebanese. The university has the role of transferringknowledge to demand, and helpingthem to carry out researchthat identifies and responds On problems, whichorganize and manage information. Researchers have akeyrole in providinganswers and practicalsolutionsTo help decision-makersachieveeconomic, educational, cultural and social goals.